Incidence and predictors of recurrent acute coronary syndrome among adult patients with acute coronary syndrome in West Amhara, Ethiopia: a multicenter retrospective follow-up study - Alamaw, Addis Wondmagegn; Asefa, Tseganesh; Abebe, Gebremeskel Kibret; Zemariam, Alemu Birara; Liyew, Bikis (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Acute coronary syndrome (ACS) is the most common cause of morbidity and mortality in patients with coronary heart disease. Furthermore, the recurrence of this problem had high adverse outcomes. However, in Ethiopia there is not enough information regarding this problem, hence this study assessed the incidence rate and its predictors of recurrence in West Amhara. Methods: A retrospective follow-up study was conducted among 469 primary ACS patients. A pre-tested structured data extraction tool was used to collect data from the patient chart. The Weibull regression analysis model was implemented and the effect size measured with an adjusted hazard ratio with 95% CI at P-value< 0.05 was inferred as statistically significant.Result: A total of 429 patients were used in the final analysis (average age, 60±13.9 years; and 245 (57.1%) men). A total of 53 patients (12.35%; 95%CI:9.55-15.83%) had recurrent ACS. The overall risk time was 93914 days (3130.47 months), and the recurrence rate was 17/1000 patients/month. Identified predictors were its typical symptoms (syncope (HR): 3.54, P=0.013), fatigue (HR: 5.23, P<0.001)), history of chronic kidney disease, (HR: 8.22, P<0.001), left ventricular ejection fraction <40% (HR: 2.34, P=0.009), not taking in-hospital treatments (aspirin (HR: 9.22, P<0.001), clopidogrel (HR: 4.11, p=0.001), statins (HR: 2.74, p=0.012)), and medication at discharge (statins (HR: 4.56, p<0.001).Conclusion: this study found a higher incidence rate of recurrent ACS. Hence, guidelinerecommended anti-ischemic treatment implementation should be strengthened.